Philosophy and political power in antiquity - Arruzza, Cinzia. (Studies in Moral Philosophy, 2016)
Philosophy and Political Power in Antiquity is a collection of essays examining ancient philosophers' reflections on the connection between political power and philosophy. The ancient Greeks both invented political philosophy and were the first to conceptualize the implicit tension between political activity and the contemplative life as found in ideal political institutions and under conditions of repressive rule. These essays examine discussions of these issues within a wide variety of the major schools of antiquity from both interpretive and analytical perspectives. While providing novel approaches to ancient philosophical texts, this volume attests to the importance of political reflection, deliberation, and resistance for ancient thought, and to the enduring strength and relevance of these reflections for contemporary debates within political philosophy.